3a(a+2)=

Simple and best practice solution for 3a(a+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a(a+2)= equation:


Simplifying
3a(a + 2) = 0

Reorder the terms:
3a(2 + a) = 0
(2 * 3a + a * 3a) = 0
(6a + 3a2) = 0

Solving
6a + 3a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '3a'.
3a(2 + a) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(2 + a)' equal to zero and attempt to solve: Simplifying 2 + a = 0 Solving 2 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + a = 0 + -2 Combine like terms: 2 + -2 = 0 0 + a = 0 + -2 a = 0 + -2 Combine like terms: 0 + -2 = -2 a = -2 Simplifying a = -2

Solution

a = {0, -2}

See similar equations:

| 4+2*n=10 | | ln(8x-1)=5 | | d^2-8d+4=0 | | 18-4*2=l | | p(p-8)= | | 18-4*2=k | | 3x+6=-45 | | 5*c=78 | | 2w+2(4w)+w=329 | | x^2+11x-28=9x-4 | | 5n+3=2n-6 | | 32+z=126 | | 2z-3z-8z+y=z | | 2z-3z-8z+y=x | | (y-2)+(y-1)+y=-3 | | 80-6x=80 | | 6(4+2w)=-2(w-10) | | 5+5x-10+8x=11 | | 16x^3y^4+14x^2y^2z+3xz^2=0 | | -4x-(6-x)=12+4x | | 6.8=5x+7.8 | | -0.09x=-3.6 | | -c=6+c | | 19t+6t=t | | x+0.08(60)=0.20(60+x) | | y-3.4=8 | | 5y+10-3y-y=-7 | | 7(x-5.1)=5.6 | | 8b+3b=b | | 2x^4-9x^3-4x^2=0 | | 8x+9.84=4x+14 | | 2w+8w+w=329 |

Equations solver categories